Buddhism: what everyone needs to know - Wright, Dale Stuart (Oxford University Press, 2020)
"Why would everyone need to know anything about Buddhism? One important reason is that no matter who you are or where you live, Buddhism is part of your cultural environment. Whether we know it or not, most of us have Buddhist neighbors or communities of Buddhists living not far away. Now more than ever before mutual understanding between people from different cultural backgrounds is crucial. We live and work together. We share the same trains, schools, shopping centers, theatres, and everything else, and mutual understanding is the key to productive, peaceful co-existence. But getting along with others isn't the only reason to introduce yourself to Buddhism, nor even the best one. There is much that all of us can learn from each other, knowledge that may in fact prove to be quite useful in shaping our own ways of living. Many of us have been doing that for decades--taking an interest in cultural, religious, and philosophical traditions different from our own as a way to stretch our minds, to broaden our understanding not just of other people but of the many admirable ways to think about the world and the many ways to live creatively and responsibly within it. In this respect many people who were not raised Buddhists have discovered that Buddhism has a lot to offer. Among the world's religions it is certainly unique. Indeed, even though Westerners have been interested in Buddhism for almost two centuries, debate still continues over what Buddhism is. Is it a religion? A philosophy? A way of life? A set of techniques for mental and psychological enhancement? It appears to function in all of these ways and continues to impress observers with the range of values it offers"--